Lamellar columnar liquid-crystalline mesophases as a 2D platform for anhydrous proton conduction. Issue 33 (12th August 2019) - Cuerva, Cristián; Campo, José A.; Cano, Mercedes; Schmidt, Rainer
Abstract : The fluid properties in the mesophase favour the dissociation of the pyrazole proton, and the metallomesogens behave as water-free proton conductors. Abstract : Several series of dihalide Pd(ii ) compounds bearing pyridyl or isoquinolinylpyrazole ligands have been strategically designed and synthesised to exhibit columnar mesomorphism in wide stability ranges. The coordination of the pyrazoles to the fragments PdX2 (X = Cl, Br, I) generates half-disc molecules that are capable of self-assembling into discotic dimers via intermolecular interactions. This disc-like shape is required for the supramolecular organisation of the lamellar columnar mesophases, which are formed at temperatures below 100 °C in most cases. It was found that these metallomesogens behave as 2D proton conducting materials under anhydrous conditions. The high fluidity properties of the mesophase facilitate proton conduction as a result of the spontaneous dissociation of the acidic pyrazole proton at the melting temperature. For the first time, lamellar columnar mesophases are demonstrated to serve as a 2D platform to induce water-free proton conductivity in dihalide Pd(ii ) metallomesogens.